Sources of Leader Support and Interstate Rivalry. Issue 5 (3rd September 2018) - Rooney, Bryan
ABSTRACT: Since segments of the selectorate differently experience costs and benefits from rivalry, the foreign policy choices of leaders reflect these domestic preferences. As a result, shifts in the composition of the domestic coalition of support backing the leader provide a fundamental determinant of rivalry termination. While previous research sought to explore the relationship between domestic political turnover and rivalry termination using regime transitions as a proxy for turnover of the state's domestic ruling group, in practice this measure exhibits significant disconnection with the quantity of interest. Further, there are alternative pathways through which regime transitions may lead to rivalry termination. I test the relationship using new data from the CHISOLS project, finding that when rivals undergo a change in the source of support that maintains the leader in office, the probability of rivalry termination rises dramatically. I further find that regime transitions have an effect on the probability of rivalry termination that is independent of the effect of ruling coalition turnover. This study thus both asserts the relationship between domestic political turnover and rivalry termination and clarifies the mechanism by which the relationship operates.